Feasibility of clinical hypnosis for transesophageal echocardiography in children and adolescents. (February 2019) - Amedro, Pascal; Gavotto, Arthur; Gelibert, Delphine; Fraysse, Virginie; De La Villeon, Gregoire; Vandenberghe, D'Arcy; Bredy, Charlene
Background: The use of hypnosis in children has been described more than two centuries ago, with a more recent research and clinical application. There is currently a good level of evidence for the efficacy of clinical hypnosis in children for minor surgery, medical procedures or pain management. The use of clinical hypnosis, in paediatric cardiology, for invasive procedures such as transesophageal echocardiography, has not been reported. Aims: This study evaluated the feasibility of clinical hypnosis in children undergoing transesophageal echocardiography. Method: This prospective, non-randomised, cross-sectional study was carried out over 24 months in a paediatric cardiology referral centre. All children aged 10–18 years requiring a transesophageal echocardiography examination, outside the operating room and the catheterisation laboratory, were eligible for the study. Children and families could choose between transesophageal echocardiography under clinical hypnosis or under general anaesthesia (<15 years) or sedation (⩾15 years). Results: We included 16 children aged 11–18 years (seven girls, mean age 14.1±2.5 years). The hypnotic state was achieved for 15 out of the 16 participating children (94%). The transesophageal echocardiography examination could be completely achieved with a full diagnosis for 15 out of 16 children (94%). In all cases, a transesophageal echocardiography examination under clinical hypnosis provided a complete diagnosis. Conclusion: This study demonstrated that hypnosis was feasible and effective for transesophageal echocardiography in adolescents and might be a good alternative to general anaesthesia. Further study with larger numbers of subjects and more diverse congenital cardiac conditions are needed to confirm the results in a more diverse sample.